Analysis of Pyrolytic Product Distribution for B3 and Non-B3 Medical Waste Pyrolysis - Rezeki, Tri Nur; Ridwan, Abrar; Meka, Wahyu; Fitri, Yulia; Mahendra, Rain Agri; Hamzah, Munawir; Widara, Laras Sita; Athala, Azzalya Putri (Universitas PGRI Madiun, 2022)
The coronavirus disease (COVID-19) has badly impacted many sectors, particularly medical waste generation in healthcare facilities. The increasing amount of medical waste poses a serious threat to health and environmental sustainability. Traditional waste processing (burning) cannot be used for B3 medical waste and is often mixed with non-B3 medical waste. This is because it potentially generates dangerous chemicals emitted into the atmosphere. Meanwhile, pyrolysis as a superior thermochemical technology is an effective solution for treating both B3 medical waste and non-B3 medical waste. The waste used in this study has good characteristics, as indicated by the low water and high fixed carbon content. The pyrolysis process yields products with economic value, such as solid, liquid, and gas products. Therefore, this study aims to determine the levels of products that can be produced from B3 and non-B3 medical waste. The results showed that rubber bands produce the highest proportion of liquid products at 44%, the highest solid products were obtained from LDPE plastic waste with a proportion of 65%, while the highest gas product was produced by mask waste at 45%. Based on the results, waste with high product yields can be used as an alternative energy source, such as gasoline, LPG, briquettes, and battery-based materials.